2008
DOI: 10.1580/07-weme-or-114.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Electrolyte Additive on Hydration and Drinking Behavior During Wildfire Suppression

Abstract: The addition of an electrolyte mixture to plain water decreased the overall fluid consumption of the water + electrolyte group by 220 mL.h(-1) (3.3 L.d(-1)). Supplementing water with electrolytes can reduce the amount of fluid necessary to consume and transport during extended activity. This can minimize carrying excessive weight, possibly reducing fatigue during extended exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 31 publications
2
44
0
1
Order By: Relevance
“…The majority of utility workers were significantly dehydrated at the commencement and cessation of a shift, a common observation for emergency responders (22,23) and miners (11,24,25) working in similar environmental conditions. Preshift dehydration combined with high sweat rates can result in deteriorating hydration status.…”
Section: Fluid Balancementioning
confidence: 87%
“…The majority of utility workers were significantly dehydrated at the commencement and cessation of a shift, a common observation for emergency responders (22,23) and miners (11,24,25) working in similar environmental conditions. Preshift dehydration combined with high sweat rates can result in deteriorating hydration status.…”
Section: Fluid Balancementioning
confidence: 87%
“…For example, several studies have reported no differences in activity levels between shifts or between 2-h periods, suggesting that firefighters pace themselves to ensure operations are completed [7,11,12]. In contrast, others have reported that physical activity levels are higher during the first wildfire shift (or 2-h period within-shift) and decrease over time [13,14]. Whilst these studies provide insights into how physical activity levels may change within- or between-shifts as a result of situational contexts (e.g., intensity of the fire), the between-person or between-group (e.g., different hydration status groups) nature of the analyses do not account for within-person effects across a shift or between shifts.…”
Section: Introductionmentioning
confidence: 99%
“…These tasks are usually performed in difficult conditions unique to wildland firefighting including inhaling smoke (Wegesser et al 2009), high environmental temperatures Budd 2001), the weight of the personal protective equipment (*6 kg) (Ruby et al 2002), and working on steep terrain . However, other than one report on heart rate and core temperature responses in wildland firefighters during training exercises , few reports on activity levels using accelerometry (Heil 2002;Cuddy et al 2007Cuddy et al , 2008, and a number of reports on remarkably normal core temperatures during wildland firefighting Cuddy et al 2008), there is a limit direct physiological monitor data (i.e., HR and core temperature) during real wildfires.…”
Section: Introductionmentioning
confidence: 99%
“…However, comparatively little information about the physiological challenges associated with wildfire firefighting is available Budd 2001;Ruby et al 2002;Heil 2002;Cuddy et al 2007). In addition, most of the studies that have been carried out with wildland firefighters have been conducted under simulated conditions Budd 2001) with few studies conducted during real wildfire suppression (Ruby et al 2002;Cuddy et al 2008). Therefore, the aim of this study was to analyze the physiological demands and thermal strain of wildland firefighters during real wildfire suppression according to the duration of firefighting activity.…”
Section: Introductionmentioning
confidence: 99%